Role of Socio-Economic Status of Family on the Utilization of Mother-Child Healthcare Services, Punjab, Pakistan - Siddique, Muhammad; Manj, Yasir Nawaz (Annals of Human and Social Sciences, 2024)
This study aimed to determine the socio-economic factors influencing maternal health care services utilization in Punjab, Pakistan. In Pakistan, various maternal and mother-child health initiatives are ongoing. Still, the impact of the family’s socio-economic status on the utilization of mother-child healthcare services is a neglected area of study. A multi-stage random sampling method was used in the sampling process. The sample consisted of 360 married women (15-49) with at least one child under five years of age. The interview Schedule was used as a research tool. Data were analyzed by using descriptive and inferential statistical techniques. It was found that most mothers were matriculated and belonged to middle class. Many mothers had 1-3 visits to clinics for antenatal care, and most received various antenatal care services. It was found the socio-economic status of mothers significantly influenced their use of mother-child health care services. There should be increased awareness campaigns about the importance of regular antenatal care visits and available services.